Conformationally flexible dendronized cyclotetraveratrylenes (CTTV)s self-organize a large diversity of chiral columnar, Frank-Kasper and quasicrystal phases. (June 2022) - Sahoo, Dipankar; Peterca, Mihai; Imam, Mohammad R.; Partridge, Benjamin E.; Xiao, Qi; Percec, Virgil
Highlights: Hierarchical self-organization. Column to column transition. Column to sphere transition. Helical columns and spherical helices. Frank-Kasper and quasicrystal periodic and quasiperiodic arrays. Abstract: Primary structure endows the tertiary structure while the tertiary structure determines the function of hierarchical self-organizations. This is a well-established fundamental principle both for biological and non-biological synthetic assemblies. The role of the conformational flexibility-rigidity in this process is less understood. Here we select the conformationally flexible monodisperse tetramer of veratrole, 2, 3, 7, 8, 12, 13, 17, 18-octamethoxy-5, 10, 15, 20-tetrahydrotetrabenzo[a, d, g, j]-cyclododecatetraene, known as cyclotetraveratrylene (CTTV) and use it as an apex model to compare with the less flexible corresponding trimer known as cyclotriveratrylenes (CTV) and with the rigid triphenylene (Tp) and 1, 3, 5-trihydroxybenzene (THB) when dendronized with libraries of self-assembling dendrons and with n-alkyl groups. Unexpectedly, a large diversity of chiral helical assemblies including supramolecular columns assembled from chiral spheres and crowns, 12-fold quasi liquid crystals (QLC), Frank-Kasper A15 (space group Pm 3 ¯ n ) but not σ phases (space group P 42 / mnm ), and supramolecular orientational memory effect (SOM) were observed in the case of the dendronized CTTV. The more rigid structures at the apex provide thermally more stable helical chiral periodic and quasiperiodic self-organizations with lowed dynamics which may facilitate the freezing of metastable rather than equilibrium structures. Conformational flexibility also changes the structure of the self-organization generated from supramolecular spheres. These experiments indicate that additional studies on the topic of conformational flexibility are desirable. Graphical abstract: Image, graphical abstract